PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT LG ELEKTRONIK INDONESIA - Diana Hayati; Penta Lestarini Budiati; Rizky Aminullah (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2020)
Abstract, This research aims to find empirical evidence that the quality of service consisting of tangible, reliability, responsiveness, assurance and empathy has a partially influential and simultaneous customer to PT LG Elektronics Indonesia’s customer satisfaction. This research method is quantitative descriptive method. The population in this research were all customers of PT LG Elektronik Indonesia, especially those domiciled in the city of Banjarmasin in 2018 as many as 5.205 people. Furthermore, samples were taken as many as 371 customers by accidental random sampling technique. Data analysis using multiple linear regression. The results of the research found that the quality of service consisting of tangible, reliability, responsiveness, assurance and empathy has a partial and simultaneous effect on customer satisfaction of PT LG Elektronics Indonesia.